Utilization of Local Sago Fiber as a Sustainable Additive in Cement Mortar - Maysyurah, Alfina; Purwantoro, Didik S; Arifin, Herlina; Fajar, Muhammad Nur; Aris, Muhammad (Program Studi Teknik Sipil Universitas Bosowa, 2026)
This study aims to evaluate the effect of adding sago fiber as an environmentally friendly additive on the physical properties of mortar, namely density, porosity, water absorption, and compressive strength. The study was conducted experimentally in the laboratory with variations of normal mortar and the addition of sago fiber of 2%, 4%, and 10%. Cubic test specimens measuring 5 × 5 × 5 cm were tested at the age of 28 days for density, porosity, water absorption, humidity and temperature, and compressive strength. The test results showed that the addition of sago fiber caused a decrease in the value of the density and compressive strength of the mortar, while the porosity and water absorption values increased. The highest density value was obtained in normal mortar at 2.09 gr/cm³ and a compressive strength of 21.33 MPa. Meanwhile, with a variation of 10% sago fiber, the density decreased to 1.53 gr/cm³ and the compressive strength only reached 3.22 MPa. Environmental conditions such as temperature and humidity also affect the compressive strength of mortar. This study concluded that sago fiber can be used as an environmentally friendly additive in mortar, but its use should be limited to maintain the material's structural performance.